Judicial Approaches to Copyright Infringement and Compensation in Indonesia’s Digital Era - Rufinus Hotmaulana Hutauruk; Retno Andarini; Nurlaily Nurlaily; Hari Sutra Disemadi (Vifada Assumption Journal of Law, 2026)
Purpose: This research identifies the gap between the ideal provisions of copyright law and its implementation in Indonesia, aiming to analyze the patterns of judicial reasoning in copyright disputes through a jurisprudential approach, and to evaluate the alignment of judicial decisions with copyright protection in the digital era. Research Design and Methodology: The research employs a normative juridical method, using statute, case, and conceptual approaches, with secondary data collected through library research to analyze relevant court decisions. Findings and Discussion: The analysis identifies a common permission-centered pattern in determining liability but a sharp divergence in determining compensation. Both courts treated ownership, commercial exploitation, and the absence of authorization as decisive. In “SKJ88,” the court compensated material and immaterial with unequal but largely adequate explanation. In “Bilang Saja,” showed inconsistency by awarding material damage while denying immaterial damage without any explanation, after transforming a fundamentally royalty dispute case into a straightforward infringement from unauthorized use. The court also did not adequately address the defense that the dispute concerned unpaid royalties governed by Government Regulation No. 56 of 2021. Implications: The findings demonstrate the need for clearer standards for civil compensation, fuller judicial engagement with applicable royalty rules and the parties’ legal arguments, and more broadly, more transparent legal reasoning in court proceedings. Such measures would improve consistency, transparency, and accountability in copyright adjudication, while also accelerating the fulfillment of SDG 16 objectives in the legal system.